Option 3 : 5 ∶ 1

**Given:**

\(a = \;\sqrt {135 + \sqrt {74 + \sqrt {43 + \sqrt {36} } } } \)

and, \(b = \;\sqrt {70 - \sqrt {41 - \sqrt {22 + \sqrt 9 } } } \)

**Calculation:**

We have, \(a = \sqrt {135 + \sqrt {74 + \sqrt {43 + \sqrt {36} } } } \)

\( ⇒ a = \sqrt {135 + \sqrt {74 + \sqrt {43 + 6} } } \)

\( ⇒ a = \sqrt {135 + \sqrt {74 + \sqrt {49} } } \)

\( ⇒ a = \sqrt {135 + \sqrt {74 + 7} } \)

\( ⇒ a = \sqrt {135 + \sqrt {81} } \)

\( ⇒ a = \sqrt {135 + 9} \)

\( ⇒ a = \sqrt {144} \)

\( ⇒ a = 12\)

and, \(b = \;\sqrt {70 - \sqrt {41 - \sqrt {22 + \sqrt 9 } } } \)

\( ⇒ b = \;\sqrt {70 - \sqrt {41 - \sqrt {22 + 3} } } \)

\( ⇒ b = \;\sqrt {70 - \sqrt {41 - \sqrt {25} } } \)

\( ⇒ b = \;\sqrt {70 - \sqrt {41 - 5} } \)

\( ⇒ b = \;\sqrt {70 - \sqrt {36} } \)

\( ⇒ b = \;\sqrt {70 - 6} \)

\( ⇒ b = \;\sqrt {64} \)

\( ⇒ b = \;8\)

Now, (a + b)/(a - b) = (12 + 8)/(12 - 8)

⇒ 20/4

⇒ 5/1

**∴ The value of (a + b) : (a - b) is 5 : 1.**